Persepsi Mahasiswa Pendidikan Agama Islam dalam Menghadapi Fenomena Childfree - Abu Amar (Cendekia, 2024)
The increasing phenomenon of childfree affects the views of Islamic religious education students regarding law, the function of marriage and children. This research explores the understanding of the childfree phenomenon from the perspective of students as potential perpetrators, supporters or opponents of childfree. This research is aim to find out their views on the meaning, response and role of Islamic education towards childfree. This research applies descriptive qualitative methods. The research results show that the definition of childfree is a situation of having a family without expecting the birth of children, delaying the birth of children, limiting the number of children and the situation of not being able to have children. Economic, social, psychological and health conditions are the causes of childfree. From the perspective of Islamic law, they agree that they will not accept childfree if the marriage is intentionally intended without expecting the presence of children, because it is contrary to their faith and the purpose of marriage. Regarding the role of Islamic education, the promotion of parental responsibility for children should be comparable to the promotion of children's obligations to be filial to their parents. Regarding their attitude towards childfree as a life choice, some stated that childfree is an individual choice that must be respected, but some rejected it because it was not following Islamic education.